Taxonomic revision of the spider genus Azilia Keyserling, 1881 (Araneae: Tetragnathidae) - BRESCOVIT, ANTONIO D.; RODRIGUES, EVERTON NEI LOPES [UNESP]; ÁLVAREZ-PADILLA, FERNANDO; OTT, RICARDO (Magnolia Press, 2025)
The species of the spider genus Azilia Keyserling, 1881 from the Americas are revised. Cardimia Mello-Leitão, 1940 is removed from the synonymy with Azilia and is newly synonymized with Diphya Nicolet, 1849, with its type species, Cardimia eximia Mello-Leitão, 1940, considered synonymous of Diphya bicolor Vellard, 1926. The genus type species, Azilia formosa Keyserling 1881 described from Peru is redescribed. The type material is considered lost, but here a neotype is designed based on specimens next to the type locality in Peru. Azilia boudeti Simon, 1895, Azilia marmorata Mello-Leitão, 1948, Arochoides integrans Mello-Leitão, 1935 and Cyrtophora vachoni Caporiacco, 1954 had their types examined and are synonymized with Azilia histrio Simon, 1895. The males of Azilia formosa and A. histrio are described for the first time. Azilia affinis O. Pickard-Cambridge, 1893, A. guatemalensis O. Pickard-Cambridge, 1889, A. rojasi Simon, 1895 and A. montana Bryant, 1940 are redescribed and illustrated. Finally, eight new species are described based on males and females, including six from Brazil: Azilia arrebitada sp. nov.; A. catita sp. nov.; A. fabulosa sp. nov.; A. guapa sp. nov.; A. joinha sp. nov.; A. supimpa sp. nov. and two from Mexico: Azilia esplendida sp. nov., and A. hermosa sp. nov.